Responsible scaling for transformative impact: Lessons from the science and practice of responsible scaling for agri-food system transformation - Kihoro, Esther; Schut, Marc; McGuire, Erin; Gebreyes, Million; Leeuwis, Cees (Elsevier, 2025)
Innovation is central to achieving global agri-food transformation agendas, including those related to the 2030 United Nations Sustainable Development Goals. The effective use of technologies, along with process and institutional innovations, at optimal scale by farmers and other diverse clients is essential to addressing interconnected challenges such as poverty, malnutrition, biodiversity loss, and climate change. Over the past decade, notions about the “scaling” of innovations have shifted from simplistic ‘copy-paste’ models to acknowledging the context-specificity, complexity, and unpredictability related to innovation use at progressively larger scales. Despite this shift, many scaling efforts remain relatively unsustainable or irresponsible. They often fail to catalyze systemic change, remain supply-driven, and lack focus beyond project lifespans. In worst case scenarios, they may also generate unintended and negative consequences rather than broad societal or environmental benefits. Approaches like mission-oriented innovation policy, transformative innovation policy, and co-production have emerged to address these persistent challenges. While they promote more inclusive and systemic innovation, their integration into scaling practice remains limited, highlighting the need for more deliberate and aligned efforts.